Research of the effects of technological factors on the quality indices of high oleic sunflower oil - Dichtyar, Aliona; Fedak, Natalia; Pyvovarov, Yevgen; Stepankova, Galyna; Yarantseva, Yevgeniia (Technology audit and production reserves, 2017)
The object of research is high oleic sunflower oil (HOSO) and refined deodorized sunflower oil (RDSO) as a control. The distinguishing characteristic of HOSO consists in the changed fatty acid composition, has a high content of triglycerides of oleic acid more than 89 %. HOSO has the following characteristics: (ρ=915...920 g/cm3, η=0.0180±0.0009 Pa, t (solidification)=0...-6 ºC, refractive index 1,466...1,468; TbN =0.0100±0.0003 mg MA/1000 g, PN=0.83±0.02 mmol ½ O/kg, SN=184...194 mg KOH, AN=0.112±0.003 mg KOH/g; IN=105±5 % I2; =3.00±0.09). One of the most problematic places for using oils is that they are faster than solid fats, refreshing products has less shelf life. In the course of the study, the influence of technological factors on the HOSO properties and the scientific basis for the HOSO use as a prescription component of food systems is determined. It is proved that during the storage HOSO is more resistant to processes in comparison with RDSO, since glycerides of polyunsaturated fatty acids oxidize faster than monounsaturated, confirming the experimental data of physicochemical parameters, fatty acid composition and dynamics of the content of tocopherols. HOSO stability for oxidation processes under conditions of prolonged thermal action in comparison with RDSO (control) by functional numbers (acid, peroxide, iodine, thiobarbituric) is studied. It is found that the oxidation rate in HOSO is lower than in theRDSO (control) by 2 times at the beginning of the heat treatment and by 1.23 times with the maximum duration of heat treatment. The coefficient of extinction grows to the limit of maximum permissible values at 6 hours in RDSO and 18 hours in HOSO, which confirms the HOSO thermal stability that is 3 times greater. Essential changes in the fatty acid composition and in the complex of tocopherols of oils under heat treatment conditions, the nature of which depends on the type of oil and the duration of heat treatment, are also shown, which also indicates a greater stability of HOSO for oxidation processes in comparison with RDSO (control). On the basis of the research, recommendations are developed on the HOSO use in the technology of custard products and as a medium for frying. Rational conditions of the brewing process are t=95...100 ºC, τ=(3...5)×60 s, hydromodule «HOSO-water» – 1:2.5. Recommended parameters for the HOSO use as a medium for frying, in particular deep-fried: t=160...180 ºC, duration of continuous use τ=(0...18)×602 s, ratio «HOSO – semifinished product» is 4: 1, HOSO storage time is 24 months. Thus, HOSO use will ensure the use of domestic raw materials; the maximum realization of the functional and technological properties of HOSO with obtaining high-quality products; reduction of energy costs and labor intensity of the process; introduction of resource-saving technologies using the newest principles of food production.